Shaping South Asia's future : role of regional cooperation - Bhargava, K. K. (Kant Kishore); Bongartz, Heinz; Sobhan, Farooq; Friedrich-Ebert-Stiftung.; Conference on "Shaping South Asia's Future: Role of Regional Cooperation" (1994 : Kathmandu, Nepal) (New Delhi : Vikas Pub. House, 1995)
Papers presented at a Conference on "Shaping South Asia's Future: Role of Regional Cooperation" in Kathmandu, 1994, organized by Friedrich-Ebert-Stiftung.
Includes bibliographical references (p. 217-220) and index.
0706992253
Keywords: South Asian Regional Cooperation -- Congresses; Regionalism -- South Asia -- Congresses; South Asia -- Politics and government -- Congresses